Ceramic glaze, preparation method and application thereof, and ceramic product

By using the combination of frits and nanomaterials in ceramic easy-to-clean glaze, the surface energy and roughness of the glaze surface are adjusted, and the super-hydrophilic effect is achieved using the redox mechanism, which solves the problems of high roughness and poor cleanliness in ceramic easy-to-clean glaze, and realizes ceramic easy-to-clean glaze with low roughness, strong hydrophilicity and good cleaning.

CN118290030BActive Publication Date: 2025-03-28SHAOGUAN LEHUA CERAMIC SANITARY WARE CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410348063.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-26
Publication Date
2025-03-28
Estimated Expiration
2044-03-26

AI Technical Summary

Technical Problem

The existing ceramic easy-to-clean glaze has high roughness and poor cleanliness, making it difficult to reduce glaze roughness and improve hydrophilicity at the same time.

Method used

Three different temperature frits (first high-temperature frit, second high-temperature frit and low-temperature frit) and their ratio regulation are adopted, and ultrafine silica, ultrafine alumina, nano zinc oxide and nanotitanium dioxide are introduced. By mixing the relative content, the glaze surface energy is improved, the micrometer size roughness is constructed, and the superhydrophilic glaze is achieved using the redox mechanism.

Benefits of technology

It has achieved ceramic easy-to-clean glaze with low roughness, strong hydrophilicity and good cleaning properties, overcomes the contradiction between roughness and hydrophilic characteristics, and improves the cleaning ability of the glaze and the effect of isolating dirt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118290030B_ABST
    Figure CN118290030B_ABST
Patent Text Reader

Abstract

The present invention discloses a ceramic glaze, a preparation method and application thereof, and a ceramic product. The super-hydrophilic ceramic easy-to-clean glaze of the present invention comprises three different temperature frits, which improve the melting degree of the glaze, reduce the number of micropores, and reduce the roughness of the glaze. The present invention regulates three different temperature frits and their proportions, introduces ultrafine silica, ultrafine alumina, etc., and adjusts the relative contents of low-temperature frits, high-temperature frits, and ultrafine silica, ultrafine alumina, etc. The obtained ceramic glaze improves the surface energy of the glaze, constructs the micron-sized roughness of the glaze, and utilizes the redox mechanism to achieve a super-hydrophilic glaze. The super-hydrophilic ceramic easy-to-clean glaze of the present invention overcomes the contradictory relationship between roughness and hydrophilicity, and achieves low roughness, strong hydrophilicity, and good easy-to-clean property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a ceramic glaze and a preparation method and application thereof, and a ceramic product. Background Art

[0002] In the ceramic industry, improving the anti-fouling property of products can make them easier to clean, thus saving water resources. Therefore, it is very important to develop ceramic easy-to-clean glazes with good anti-fouling properties. The easy-to-clean property of ceramic glazes is related to the roughness and hydrophilicity of the ceramic glazes. The roughness of ordinary easy-to-clean glazes is 0.08-0.12μm, the contact angle is 20-40°, and the roughness of ordinary white glazes is >0.1μm, and the contact angle is 15-30°. The greater the roughness of the glaze, the more pores, the greater the surface energy, and the smaller the contact angle; however, as the roughness of the glaze increases, the dirt storage capacity increases, which also leads to a decrease in the easy-to-clean ability.

[0003] In the related art, the application of easy-to-clean ceramic glaze generally adopts the method of base glaze + top glaze. This method mainly adjusts the top glaze to form a layer of glass with low roughness on the glaze surface to achieve the purpose of easy cleaning. However, this method has many disadvantages: the base glaze is a high-temperature opalescent white glaze, and the top glaze is a relatively low-temperature transparent glaze. The low-temperature top glaze has a low initial melting point, and the liquid phase produced in advance plays a sealing role. The gas of the body and the base glaze cannot be discharged normally, resulting in many pores on the surface of the ceramic product, high roughness, and low easy cleaning performance; if the temperature of the top glaze is increased, the melting effect of the top glaze is poor, and the refractory materials such as quartz are not completely melted, and the poor fluidity of the top glaze causes the gas generated by the body and the base glaze to escape to form pits and micropores that cannot be filled, which will also increase the roughness of the ceramic product and reduce the easy cleaning ability.

[0004] Therefore, it is of great significance to solve the problems of high roughness and poor cleanability in ceramic glazes, overcome the contradictory relationship between glaze roughness and hydrophilicity, and provide a ceramic easy-to-clean glaze with low roughness and strong hydrophilicity. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a ceramic glaze and a preparation method and application thereof, and a ceramic product, aiming to solve the problems of high roughness and poor cleanability existing in the current ceramic easy-to-clean glaze, and provide a super hydrophilic easy-to-clean glaze with low roughness.

[0006] The first aspect of the present invention provides a ceramic glaze, which includes, by mass, 45 to 70 parts of a first high-temperature frit, 10 to 20 parts of a second high-temperature frit, 5 to 15 parts of a low-temperature frit, 10 to 25 parts of ultrafine silicon dioxide, 0 to 6 parts of ultrafine aluminum oxide, 0 to 10 parts of nano zinc oxide, and 0 to 10 parts of nano titanium dioxide; the mass fractions of the ultrafine aluminum oxide, nano zinc oxide, and nano titanium dioxide are not all 0 at the same time.

[0007] The ceramic glaze according to the embodiment of the present invention has at least the following beneficial effects: The present invention proposes a super-hydrophilic ceramic easy-to-clean glaze, which improves the melting degree of the glaze, reduces the number of micropores, and reduces the roughness of the glaze through three different temperature frits. Among them, the first high-temperature frit has a high initial melting temperature, a large surface tension, and a large high-temperature viscosity; the second high-temperature frit has a relatively high initial melting temperature, a large surface tension, and a large high-temperature viscosity; the low-temperature frit has a low initial melting temperature, a small surface tension, and a low high-temperature viscosity. The present invention uses the first high-temperature frit as the main raw material of the hydrophilic glaze, and its firing temperature is higher than that of the opalescent white glaze, and the surface tension is large; the second high-temperature frit and the low-temperature frit jointly adjust the glaze temperature, tension, and viscosity, and the whole constitutes a system for adjusting the glaze temperature, tension, and viscosity in multiple directions, so that the micropores on the glaze surface are reduced to the minimum value, and low roughness is achieved. Ultrafine silica and ultrafine alumina play the role of increasing the initial melting temperature, increasing the surface tension, and increasing the high-temperature viscosity. The introduction of ultrafine alumina and ultrafine silica can shorten the ball milling time during the preparation of the glaze slurry, reduce the particle size of the glaze slurry, and reduce the roughness of the glaze surface. Nano zinc oxide and nano titanium dioxide have strong activity and strong fluxing ability. The early generation of liquid phase can increase the micropore gaps on the glaze surface. Finally, the present invention regulates three different temperature frits and their ratios, and introduces ultrafine silica, ultrafine alumina, etc., and adjusts the relative content of low-temperature frits, high-temperature frits, and ultrafine silica, ultrafine alumina, etc. The obtained ceramic glaze improves the surface energy of the glaze surface, constructs the micron-sized roughness of the glaze surface, and utilizes the redox mechanism to achieve a super-hydrophilic glaze surface. Not only that, the glaze of the present invention also reduces the micropore gaps caused by the exhaust of the body glaze, and also achieves the purpose of reducing roughness. The super-hydrophilic ceramic easy-to-clean glaze of the present invention overcomes the contradictory relationship between roughness and hydrophilicity, and achieves low roughness, strong hydrophilicity, and good easy-to-clean property.

[0008] In some embodiments of the present invention, the first high-temperature molten block includes silicon dioxide (SiO2), aluminum oxide (Al2O3), calcium oxide (CaO), magnesium oxide (MgO), potassium oxide (K2O), and sodium oxide (Na2O).

[0009] In some preferred embodiments of the present invention, the first high-temperature molten block includes, by mass, 62 to 65 parts of silicon dioxide, 8 to 10 parts of aluminum oxide, 10 to 15 parts of calcium oxide, 1 to 2 parts of magnesium oxide, 3 to 5 parts of potassium oxide, and 1 to 2 parts of sodium oxide.

[0010] In some preferred embodiments of the present invention, the first high-temperature molten block further includes ferric oxide (Fe2O3), titanium dioxide (TiO2), zinc oxide (ZnO), and barium oxide (BaO).

[0011] In some preferred embodiments of the present invention, the first high-temperature molten block further comprises, by weight, 0-0.2 parts of ferric oxide, 0-0.1 parts of titanium dioxide, 0-2 parts of zinc oxide, and 0-6 parts of barium oxide.

[0012] Specifically, calculated by mass, the first high-temperature molten block includes 62 to 65 parts of silicon dioxide, 8 to 10 parts of aluminum oxide, 10 to 15 parts of calcium oxide, 1 to 2 parts of magnesium oxide, 3 to 5 parts of potassium oxide, 1 to 2 parts of sodium oxide, 0 to 0.2 parts of iron oxide, 0 to 0.1 parts of titanium dioxide, 0 to 2 parts of zinc oxide, and 0 to 6 parts of barium oxide.

[0013] In some embodiments of the present invention, the second high-temperature molten block includes silicon dioxide (SiO2), aluminum oxide (Al2O3), calcium oxide (CaO), magnesium oxide (MgO), potassium oxide (K2O), sodium oxide (Na2O), and zinc oxide (ZnO).

[0014] In some preferred embodiments of the present invention, the second high-temperature fused block includes, by mass, 62 to 65 parts of silicon dioxide, 10 to 14 parts of aluminum oxide, 8 to 10 parts of calcium oxide, 1 to 2 parts of magnesium oxide, 2 to 6 parts of potassium oxide, 1 to 3 parts of sodium oxide, and 5 to 8 parts of zinc oxide.

[0015] In some preferred embodiments of the present invention, the second high-temperature molten block further includes ferric oxide (Fe2O3) and titanium dioxide (TiO2).

[0016] In some preferred embodiments of the present invention, the second high-temperature molten block further comprises 0-0.2 parts of ferric oxide and 0-0.1 parts of titanium dioxide, calculated by weight.

[0017] Specifically, calculated by mass, the second high-temperature molten block includes 62 to 65 parts of silicon dioxide, 10 to 14 parts of aluminum oxide, 8 to 10 parts of calcium oxide, 1 to 2 parts of magnesium oxide, 2 to 6 parts of potassium oxide, 1 to 3 parts of sodium oxide, 5 to 8 parts of zinc oxide, 0 to 0.2 parts of iron oxide, and 0 to 0.1 parts of titanium dioxide.

[0018] In some embodiments of the present invention, the low-temperature frit includes silicon dioxide (SiO2), aluminum oxide (Al2O3), calcium oxide (CaO), and sodium oxide (Na2O).

[0019] In some preferred embodiments of the present invention, the low-temperature frit includes, by mass, 65-68 parts of silicon dioxide, 4-6 parts of aluminum oxide, 6-9 parts of calcium oxide, and 10-15 parts of sodium oxide.

[0020] In some preferred embodiments of the present invention, the low-temperature sintered block further comprises ferric oxide (Fe2O3), titanium dioxide (TiO2), magnesium oxide (MgO), potassium oxide (K2O), and zinc oxide (ZnO).

[0021] In some preferred embodiments of the present invention, the low-temperature frit further comprises, by weight, 0-0.2 parts of ferric oxide, 0-0.1 parts of titanium dioxide, 0-1 parts of magnesium oxide, 0-2 parts of potassium oxide, and 0-2 parts of zinc oxide.

[0022] Specifically, calculated by mass, the low-temperature fused block includes 65-68 parts of silicon dioxide, 4-6 parts of aluminum oxide, 6-9 parts of calcium oxide, 10-15 parts of sodium oxide, 0-0.2 parts of iron oxide, 0-0.1 parts of titanium dioxide, 0-1 parts of magnesium oxide, 0-2 parts of potassium oxide, and 0-2 parts of zinc oxide.

[0023] In the present invention, the silicon and aluminum contents of the three kinds of frits are different, and the contents and types of fluxes are also different, so the effects produced by each are also different. Among them, the high and low temperatures of the frit are related to its silicon and aluminum content and flux content: the Si network body and Al in the components are network intermediates, which are the glaze skeleton network; K, Na, Ca, Mg, Ba, Zn, etc. are all network destroyers. According to the strength of fluxing ability, it is roughly Na>K>Zn>Ti>Ca>Mg>Ba, among which K and Na have the strongest network destructive ability. The higher their content, the lower the glaze temperature and the worse the glaze performance. The present invention obtains three kinds of frits with different melting temperatures and functions by reasonably regulating the silicon and aluminum content, the content and type of flux in the frit components: the first high-temperature frit has a high initial melting temperature, a large surface tension, and a large high-temperature viscosity; the second high-temperature frit has a high initial melting temperature, a large surface tension, and a large high-temperature viscosity; the low-temperature frit has a low initial melting temperature, a small surface tension, and a low high-temperature viscosity. By adjusting the number of frits at three different temperatures, the surface energy of the glaze was improved, the micron-sized roughness of the glaze was constructed, and the redox mechanism was utilized to achieve a super-hydrophilic glaze.

[0024] At present, super-hydrophilic easy-to-clean glaze has not been applied in the field of sanitary ceramics. There are two types of super-hydrophilic mechanisms. One is the surface structural roughness of high surface energy materials. The surface structural roughness can be roughly divided into three states: micron size, micro-nano size and porous state; the second is the photo-induced super-hydrophilic mechanism. The photo-induced super-hydrophilic mechanism is divided into two types, one is the photocatalytic mechanism and the other is the redox mechanism. For sanitary ceramic glaze, due to its usage characteristics, constructing a porous state and micron size to make the glaze super-hydrophilic is not in line with actual use. Even if the glaze is in a super-hydrophilic state, the porous state and micron size will hide dirt and are not conducive to cleaning. Using the construction of micron size and porous state roughness to achieve super-hydrophilicity cannot achieve the purpose of easy cleaning. The present invention utilizes the redox mechanism: utilizing the activity of nano zinc oxide and nano titanium dioxide to give the glaze a high surface energy, thereby forming a highly hydrophilic area at the microscopic level; at the microscopic level, micropores under the action of high surface tension form smooth small peaks, thereby constructing micro-nano size roughness, so that the glaze surface can reach a super hydrophilic state and the macroscopic roughness of the glaze surface is small, thereby ultimately achieving a super hydrophilic glaze surface.

[0025] In some embodiments of the present invention, the ceramic glaze includes at least one of ultrafine alumina, nano zinc oxide, and nano titanium dioxide.

[0026] In some preferred embodiments of the present invention, the ceramic glaze includes ultrafine alumina, and at least one of nano zinc oxide and nano titanium dioxide.

[0027] Alumina and silica have high hardness, and it is difficult to ball-mill them to a certain particle size, which requires a long ball-milling time; and alumina and silica with large particle size have a long melting time and high melting temperature at high temperature, which will lead to increased glaze surface roughness. The present invention can shorten the ball-milling time, reduce the glaze slurry particle size, and reduce the glaze surface roughness by introducing ultrafine silica and ultrafine alumina into the glaze.

[0028] At present, super-hydrophilic easy-to-clean glaze has not been applied in the field of sanitary ceramics. There are two types of super-hydrophilic mechanisms. One is the surface structural roughness of high surface energy materials. The surface structural roughness can be roughly divided into three states: micron size, micro-nano size and porous state; the second is the photo-induced super-hydrophilic mechanism. The photo-induced super-hydrophilic mechanism is divided into two types, one is the photocatalytic mechanism and the other is the redox mechanism. For sanitary ceramic glaze, due to its usage characteristics, constructing a porous state and micron size to make the glaze super-hydrophilic is not in line with actual use. Even if the glaze is in a super-hydrophilic state, the porous state and micron size will hide dirt and are not conducive to cleaning. Using the construction of micron size and porous state roughness to achieve super-hydrophilicity cannot achieve the purpose of easy cleaning. The present invention utilizes the redox mechanism, introduces at least one of nano zinc oxide and nano titanium dioxide, utilizes the activity of nano zinc oxide and nano titanium dioxide, gives the glaze surface high surface energy, forms a high micro-hydrophilic area at the microscopic level; at the microscopic level, the micropores form smooth small convex peaks under the action of high surface tension, constructs micro-nano size roughness, and can make the glaze surface reach a super-hydrophilic state and the glaze surface has a small macroscopic roughness, and finally realizes a super-hydrophilic glaze surface. In addition, the present invention also effectively reduces the micropore gap caused by the exhaust of the body glaze due to the presence of nano zinc oxide and nano titanium dioxide, and also achieves the purpose of reducing roughness.

[0029] In some embodiments of the present invention, the particle size of the ultrafine silica is ≤10 μm.

[0030] Preferably, the proportion of particles with a particle size of ≤10 μm in the ultrafine silicon dioxide is greater than 90%, more preferably 90-95%.

[0031] In some embodiments of the present invention, the particle size of the ultrafine alumina is ≤10 μm.

[0032] Preferably, the proportion of particles with a particle size of ≤10 μm in the ultrafine alumina is greater than 90%, more preferably 90-95%.

[0033] In some embodiments of the present invention, the particle size of the nano zinc oxide is ≤100 nm, preferably 30 to 60 nm, and more preferably about 50 nm.

[0034] In some embodiments of the present invention, the specific surface area of ​​the nano zinc oxide is greater than 4 m / g, preferably 4-7 m / g.

[0035] In some embodiments of the present invention, the particle size of the nano titanium dioxide is ≤100 nm, preferably 30 to 60 nm, and more preferably about 50 nm.

[0036] In some embodiments of the present invention, the specific surface area of ​​the nano-titanium dioxide is greater than 4 m / g, preferably 4 to 7 m / g.

[0037] Finally, the present invention solves the contradictory relationship between glaze roughness and hydrophilicity by regulating several key raw materials such as low-temperature frit, first high-temperature frit, second high-temperature frit, introducing ultrafine silicon dioxide, ultrafine alumina, nano zinc oxide, and nano titanium dioxide, and rationally proportioning their components, thereby reducing the glaze roughness, improving the glaze surface energy, constructing the micron-sized roughness of the glaze, and utilizing the redox mechanism to achieve a super-hydrophilic glaze.

[0038] In some embodiments of the present invention, the roughness of the glaze surface of the ceramic glaze is 0.015-0.025 μm, and the contact angle is 5-10°.

[0039] The super-hydrophilic easy-to-clean glaze provided by the present invention realizes macroscopic low roughness and super-hydrophilic performance of the glaze surface by constructing micro-nano roughness, improving the surface energy of the glaze surface, and reducing the glaze particle size. Compared with ordinary glaze surfaces, the adhesion of dirt to the glaze surface is weakened. During repeated washing, ordinary high-roughness glaze surfaces are obviously contaminated, while the low-roughness glaze surface of the present invention is smooth and dirt is easier to wash away.

[0040] During daily use, dust in the environment and dirt in the water will be adsorbed on the glaze surface. If it is not used or cleaned for a long time, it will scale and turn yellow. Some sanitary ceramics will give the glaze a layer of water film to isolate dirt, but ordinary ceramic glazes have poor hydrophilicity, and the water film condenses into water droplets in a short time, with poor isolation effect; the super-hydrophilic glaze of the present invention can overcome this problem very well. Due to its good hydrophilic properties, its water film will not condense, and the isolation effect is good, which greatly improves the yellowing problem. Compared with ordinary ceramic glazes with higher roughness and poor hydrophilicity, low-roughness super-hydrophilic glazes are easier to clean.

[0041] The second aspect of the present invention provides a method for preparing a glaze slurry of the ceramic glaze, comprising the following steps: mixing the ceramic glaze into a ball mill according to the raw material ratio and performing wet ball milling to obtain the glaze slurry.

[0042] In some embodiments of the present invention, in the glaze slurry, particles with a particle size of less than 10 μm account for 90-95% of the total weight of the glaze slurry.

[0043] The method for preparing the glaze slurry of the ceramic glaze according to the embodiment of the present invention has at least the following beneficial effects: The preparation method of the present invention has a simple process, is closer to production, and can be directly industrialized. The introduction of ultrafine alumina and ultrafine silica can shorten the ball milling time and reduce the particle size of the glaze slurry. The particle size of the glaze slurry is controlled, and the glaze particles with a particle size below 10μm account for 90-95% of the glaze slurry (the residue on the 325 mesh sieve is about 0). The smaller the glaze particle size, the better the glaze melting effect, the more complete the melting of the refractory material, and the lower the glaze roughness. The present invention achieves ultra-low roughness by controlling the particle size of the glaze slurry, thereby improving the cleaning ability of the glaze surface.

[0044] Traditional ceramic easy-to-clean glaze has large glaze particle size and high roughness. If the glaze particle size is reduced, the glaze thickness will exceed 0.4mm, which will cause the glaze surface to crack and lead to glaze shrinkage.

[0045] In order to solve the above problem, the third aspect of the present invention provides a composite glaze, which includes a base glaze and a surface glaze, wherein the surface glaze is applied to the upper surface of the base glaze.

[0046] The bottom glaze includes an opaque glaze, and the top glaze includes the above-mentioned ceramic glaze.

[0047] The composite glaze according to the embodiment of the present invention has at least the following beneficial effects: the present invention provides a super composite glaze suitable for opalescent glaze and double-layer glazing process, by covering the surface of the opalescent glaze with the above-mentioned super hydrophilic ceramic easy-to-clean glaze with a thickness of 0.1 to 0.2 mm, and using the two-layer glazing technology to solve the glaze shrinkage problem caused by too small glaze particle size and too thick glaze layer. At the same time, by controlling the thickness of the glaze layer, the glaze shrinkage defect caused by too fine glaze is solved. Finally, without changing the whiteness, the composite glaze provided by the present invention has lower cost, smooth low-roughness glaze surface, warm texture, better easy-to-clean ability, is closer to production, and can be directly industrialized.

[0048] In some embodiments of the present invention, the opacified glaze is an opacified white glaze.

[0049] In some embodiments of the present invention, the opalescent glaze includes, by mass fraction, 60-65% silicon dioxide (SiO2), 8-12% aluminum oxide (Al2O3), 10-14% calcium oxide (CaO), 1-2% magnesium oxide (MgO), 2-4% sodium oxide (Na2O), 5-12% zirconium dioxide (ZrO2), 0-1.2% iron oxide (Fe2O3), 0-2% potassium oxide (K2O), and 0-0.5% silicon dioxide (SiO2).

[0050] A fourth aspect of the present invention provides a method for preparing a ceramic product, comprising the following steps:

[0051] S1. providing a blank;

[0052] S2, applying glaze slurry of a base glaze to the body, wherein the base glaze comprises an opalescent glaze;

[0053] S3, applying glaze slurry of the top glaze to the bottom glaze, wherein the top glaze comprises the ceramic glaze as described above;

[0054] S4, after glazing is completed, the ceramic product is fired in a kiln to obtain the ceramic product.

[0055] In some embodiments of the present invention, the green body is a product green body made of existing common sanitary ceramic slurry raw materials.

[0056] In some embodiments of the present invention, the glaze layer of the base glaze has a thickness of 0.4 to 0.6 mm.

[0057] In some embodiments of the present invention, the glaze layer thickness of the top glaze is 0.1-0.2 mm.

[0058] In some embodiments of the present invention, the firing temperature of the kiln is 1185-1210°C.

[0059] In some embodiments of the present invention, the heat preservation time for firing in the kiln is 10 to 30 minutes, preferably 15 minutes.

[0060] In some embodiments of the present invention, the firing period of the kiln is 13 to 18 hours, preferably 14 hours.

[0061] The method for preparing ceramic products according to the embodiment of the present invention has at least the following beneficial effects: the firing method of the present invention solves the glaze shrinkage problem caused by too small glaze particle size and too thick glaze layer by covering the surface of the opalescent glaze with a layer of the above-mentioned super-hydrophilic easy-to-clean glaze with a thickness of 0.1 to 0.2 mm through the two-layer glazing technology. In addition, the present invention provides a high-efficiency production rhythm solution that can solve low-temperature fast firing. With the change of glaze, the firing can be completed within the range of 1185°C to 1210°C within as low as 13 hours, which can be directly industrialized.

[0062] The fifth aspect of the present invention provides a ceramic product, which is prepared by the above-mentioned preparation method.

[0063] In some embodiments of the present invention, the roughness of the glaze surface of the ceramic product is 0.015-0.025 μm, and the contact angle is 5-10°.

[0064] The ceramic products according to the embodiments of the present invention have at least the following beneficial effects: The ceramic products provided by the present invention adopt the above-mentioned super-hydrophilic easy-to-clean glaze, and realize the macroscopic low roughness and super-hydrophilic performance of the glaze by constructing micro-nano size roughness, improving the surface energy of the glaze, and reducing the glaze particle size. Compared with ordinary glaze, the adhesion of dirt to the glaze is weakened. During repeated rinsing, the ordinary high-roughness glaze surface is obviously contaminated, and the low-roughness glaze of the present invention is smooth, and the dirt is easier to rinse off.

[0065] During daily use, dust in the environment and dirt in the water will be adsorbed on the ceramic glaze. If it is not used for a long time or not cleaned, it will scale and turn yellow. Some sanitary ceramics will give the glaze a layer of water film to isolate dirt, but ordinary ceramic glazes have poor hydrophilicity, and the water film condenses into water droplets in a short time, and the isolation effect is poor; the ceramic products of the present invention use super-hydrophilic glaze, which can overcome this problem well. Due to its good hydrophilic properties, the water film will not condense, the isolation effect is good, and the yellowing problem is greatly improved. Compared with ordinary ceramic glazes with higher roughness and poor hydrophilicity, low-roughness super-hydrophilic glazes are easier to clean. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0067] Figure 1 This is one of the test results of the roughness test of the sample in Example 1 of the present invention;

[0068] Figure 2 This is one of the test results of the contact angle test of the sample in Example 1 of the present invention. DETAILED DESCRIPTION

[0069] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0070] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0071] In the description of the present invention, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are real numbers. Unless otherwise specified, each reaction or operation step may be performed in sequence or not. Preferably, the reaction method of the present invention is performed in sequence.

[0072] If no specific techniques or conditions are specified in the following examples, the techniques or conditions described in the literature in the art or the product instructions are used. All reagents or instruments without manufacturer specified are conventional products that can be purchased commercially.

[0073] Example 1

[0074] The formula of the glaze in this embodiment is:

[0075] 60 parts of the first high-temperature frit, 15 parts of the second high-temperature frit, 10 parts of the low-temperature frit, 15 parts of ultrafine silicon dioxide, 4 parts of ultrafine aluminum oxide, 2 parts of nano zinc oxide, and 7 parts of nano titanium dioxide.

[0076] The composition of the frit is shown in Table 1:

[0077] Table 1 (All the numbers shown in the table are in mass fractions)

[0078] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> <![CDATA[TiO2]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> ZnO BaO The first high temperature frit 63.76 8.35 0.19 0.06 14.65 1.73 3.4 0.72 1.06 4.58 Second high temperature frit 63.39 13.87 0.07 0.08 8.45 1.65 4.19 1.15 7.16 0 Low temperature frit 66.57 4.07 0.04 0.06 7.77 0.17 0.27 11.96 0.3 0

[0079] Example 2

[0080] The difference from Example 1 is that the glaze formula is different. The composition of the frit is the same as that in Table 1.

[0081] The formula of the glaze in this embodiment is:

[0082] 45 parts of the first high-temperature frit, 20 parts of the second high-temperature frit, 15 parts of the low-temperature frit, 10 parts of ultrafine silicon dioxide, 6 parts of ultrafine aluminum oxide, 0 parts of nano zinc oxide, and 3 parts of nano titanium dioxide.

[0083] Example 3

[0084] The difference from Example 1 is that the glaze formula is different. The composition of the frit is the same as that in Table 1.

[0085] The formula of the glaze in this embodiment is:

[0086] 60 parts of the first high-temperature frit, 15 parts of the second high-temperature frit, 10 parts of the low-temperature frit, 25 parts of ultrafine silicon dioxide, 4 parts of ultrafine aluminum oxide, 8 parts of nano zinc oxide, and 0 parts of nano titanium dioxide.

[0087] Example 4

[0088] The difference from Example 1 is that the glaze formula is different. The composition of the frit is the same as that in Table 1.

[0089] The formula of the glaze in this embodiment is:

[0090] 70 parts of the first high-temperature frit, 10 parts of the second high-temperature frit, 5 parts of the low-temperature frit, 20 parts of ultrafine silicon dioxide, 2 parts of ultrafine aluminum oxide, 4 parts of nano zinc oxide, and 4 parts of nano titanium dioxide.

[0091] Example 5

[0092] The difference from Example 1 is that the glaze formula is different. The composition of the frit is the same as that in Table 1.

[0093] The formula of the glaze in this embodiment is:

[0094] 50 parts of the first high-temperature frit, 20 parts of the second high-temperature frit, 10 parts of the low-temperature frit, 20 parts of ultrafine silicon dioxide, 2 parts of ultrafine aluminum oxide, 4 parts of nano zinc oxide, and 4 parts of nano titanium dioxide.

[0095] Example 6

[0096] The difference from Example 1 is that the glaze formula is different. The composition of the frit is the same as that in Table 1.

[0097] The formula of the glaze in this embodiment is:

[0098] 60 parts of the first high-temperature frit, 10 parts of the second high-temperature frit, 15 parts of the low-temperature frit, 20 parts of ultrafine silicon dioxide, 2 parts of ultrafine aluminum oxide, 4 parts of nano zinc oxide, and 4 parts of nano titanium dioxide.

[0099] Example 7

[0100] The difference from Example 1 is that the glaze formula is different. The composition of the frit is the same as that in Table 1.

[0101] The formula of the glaze in this embodiment is:

[0102] 45 parts of the first high-temperature frit, 20 parts of the second high-temperature frit, 10 parts of the low-temperature frit, 25 parts of ultrafine silicon dioxide, 6 parts of ultrafine aluminum oxide, 2 parts of nano zinc oxide, and 10 parts of nano titanium dioxide.

[0103] Example 8

[0104] The difference from Example 1 is that the composition of the frit is different.

[0105] The formula of the glaze in this embodiment is:

[0106] 60 parts of the first high-temperature frit, 15 parts of the second high-temperature frit, 10 parts of the low-temperature frit, 15 parts of ultrafine silicon dioxide, 4 parts of ultrafine aluminum oxide, 2 parts of nano zinc oxide, and 7 parts of nano titanium dioxide.

[0107] The composition of the frit is shown in Table 2:

[0108] Table 2 (All the numbers shown in the table are in mass fractions)

[0109] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> <![CDATA[TiO2]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> ZnO BaO The first high temperature frit 62.4 8.35 0.19 0.06 14.65 1.73 3.4 0.72 1.06 5.92 Second high temperature frit 64.95 13.87 0.07 0.08 8.45 1.65 4.19 1.15 5.6 0 Low temperature frit 67.9 4.07 0.04 0.06 7.77 0.17 0.27 10.63 0.3 0

[0110] Example 9

[0111] The difference from Example 1 is that the composition of the frit is different.

[0112] The formula of the glaze in this embodiment is:

[0113] 60 parts of the first high-temperature frit, 15 parts of the second high-temperature frit, 10 parts of the low-temperature frit, 15 parts of ultrafine silicon dioxide, 4 parts of ultrafine aluminum oxide, 2 parts of nano zinc oxide, and 7 parts of nano titanium dioxide.

[0114] The composition of the frit is shown in Table 3:

[0115] Table 3 (All the numbers shown in the table are in mass fractions)

[0116] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> <![CDATA[TiO2]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> ZnO BaO The first high temperature frit 64.98 8.35 0.18 0.04 14.53 1.67 3.6 0.74 1.10 3.36 Second high temperature frit 62.64 13.97 0.02 0.04 8.31 1.67 4.19 1 7.91 0 Low temperature frit 65.1 4.5 0.03 0.01 6.66 0.11 0.20 14.3 0.1 0

[0117] Comparative Example 1

[0118] This comparative example does not contain the first high-temperature frit. The compositions of other frits are the same as those in Table 1.

[0119] The formula of the glaze in this comparative example is:

[0120] 0 parts of the first high temperature frit, 50 parts of the second high temperature frit, 15 parts of the low temperature frit, 15 parts of ultrafine silicon dioxide, 4 parts of ultrafine aluminum oxide, 2 parts of nano zinc oxide, and 7 parts of nano titanium dioxide.

[0121] Comparative Example 2

[0122] This comparative example does not contain the second high temperature frit. The compositions of other frits are the same as those in Table 1.

[0123] The formula of the glaze in this comparative example is:

[0124] 70 parts of the first high-temperature frit, 0 parts of the second high-temperature frit, 15 parts of the low-temperature frit, 15 parts of ultrafine silicon dioxide, 4 parts of ultrafine aluminum oxide, 2 parts of nano zinc oxide, and 7 parts of nano titanium dioxide.

[0125] Comparative Example 3

[0126] This comparative example does not contain low temperature frit. The composition of other frits is the same as that in Table 1.

[0127] The formula of the glaze in this comparative example is:

[0128] 60 parts of the first high-temperature frit, 10 parts of the second high-temperature frit, 0 parts of the low-temperature frit, 15 parts of ultrafine silicon dioxide, 4 parts of ultrafine aluminum oxide, 2 parts of nano zinc oxide, and 7 parts of nano titanium dioxide.

[0129] Comparative Example 4

[0130] The formula of the glaze in this comparative example is:

[0131] 45 parts of the first high-temperature frit, 35 parts of the second high-temperature frit, 10 parts of the low-temperature frit, 15 parts of ultrafine silicon dioxide, 4 parts of ultrafine aluminum oxide, 2 parts of nano zinc oxide, and 7 parts of nano titanium dioxide.

[0132] The composition of the frit is the same as that in Table 1.

[0133] Comparative Example 5

[0134] The formula of the glaze in this comparative example is:

[0135] 45 parts of the first high-temperature frit, 20 parts of the second high-temperature frit, 30 parts of the low-temperature frit, 15 parts of ultrafine silicon dioxide, 4 parts of ultrafine aluminum oxide, 2 parts of nano zinc oxide, and 7 parts of nano titanium dioxide.

[0136] The composition of the frit is the same as that in Table 1.

[0137] Comparative Example 6

[0138] The formula of the glaze in this comparative example is:

[0139] 30 parts of the first high-temperature frit, 30 parts of the second high-temperature frit, 20 parts of the low-temperature frit, 15 parts of ultrafine silicon dioxide, 4 parts of ultrafine aluminum oxide, 2 parts of nano zinc oxide, and 7 parts of nano titanium dioxide.

[0140] The composition of the frit is the same as that in Table 1.

[0141] Comparative Example 7

[0142] The difference from Example 1 is that ultrafine silicon dioxide and ultrafine aluminum oxide are replaced by ordinary silicon dioxide and aluminum oxide.

[0143] The formula of the glaze in this comparative example is: 60 parts of the first high-temperature frit, 15 parts of the second high-temperature frit, 10 parts of the low-temperature frit, 15 parts of ordinary silicon dioxide, 4 parts of ordinary aluminum oxide, 2 parts of nano zinc oxide, and 7 parts of nano titanium dioxide.

[0144] The composition of the frit is the same as that in Table 1.

[0145] Comparative Example 8

[0146] Ordinary white glaze on the market.

[0147] Roughness test

[0148] Test Method

[0149] The samples made of the same material as the product and prepared under the same process conditions are used as the test specimens. The sample specifications are 100mm*100mm and the number is three. According to the GB / T1031-2009 standard for surface roughness evaluation parameters, the profile arithmetic mean deviation Ra is used to characterize the roughness. The TR210 surface roughness tester is used to set the test stroke to 5mm. Five points are randomly selected from each piece to obtain the average value of the profile arithmetic mean deviation Ra. The test results are expressed as the average value of the test results of 3 pieces.

[0150] Figure 1 The figure shows the roughness test results of the glaze according to the embodiment of the present invention, specifically one of the test results of the roughness test of the sample in embodiment 1.

[0151] Contact angle test

[0152] Test Method

[0153] The samples made of the same material as the product and prepared under the same process conditions are used as test specimens. The sample specifications are 100mm*100mm and the number is three. Grade 3 water that meets the requirements of GB / T 6682 is used as the reagent. The reagent volume for each test is 2μL. The test is carried out according to the method in Appendix B of JC / T2168-2013. The data is read when there is no obvious change in the droplet shape (generally within 10 seconds). Take 2 test segments with different positions for each piece. Take 8 test points equidistantly from the end point on each test segment. The average value of the total 16 test points is taken as the contact angle value of the sample. The test results are expressed as the average value of the test results of 3 tests.

[0154] Figure 2 FIG. 1 is a schematic diagram of the contact angle test results of the glaze according to the embodiment of the present invention, specifically one of the test results of the contact angle test of Embodiment 1. FIG.

[0155] The test results are shown in Table 4:

[0156] Table 4

[0157]

[0158]

[0159] It can be seen from Examples 1-7 and Comparative Example 8 that, compared with ordinary glazes, the roughness and contact angle of the super-hydrophilic easy-to-clean glaze of the present invention are significantly smaller. It can be seen from Examples 1-7 and Comparative Example 1-3 that if the frit component is missing, the roughness of the glaze surface increases and the contact angle increases relatively; it can be seen from Examples 1-7 and Comparative Examples 4-6 that the ratio of the frit components is unreasonable, and the roughness will also increase accordingly; it can be seen from Examples 1-7 and Comparative Example 7 that the use of ordinary silica and alumina in the glaze will lead to poor glaze melting effect and high roughness. The present invention regulates three different temperature frits and their ratios, and introduces ultrafine silica, ultrafine alumina, etc., and by adjusting the relative contents of low-temperature frits, high-temperature frits, and ultrafine silica, ultrafine alumina, etc., the ceramic glaze obtained improves the surface energy of the glaze, constructs the micron-sized roughness of the glaze, and utilizes the redox mechanism to achieve a super-hydrophilic glaze.

[0160] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A ceramic glaze, characterized in that: The ceramic glaze comprises, by weight, 45 to 70 parts of a first high-temperature frit, 10 to 20 parts of a second high-temperature frit, 5 to 15 parts of a low-temperature frit, 10 to 25 parts of ultrafine silicon dioxide, 0 to 6 parts of ultrafine aluminum oxide, 0 to 10 parts of nano zinc oxide, and 0 to 10 parts of nano titanium dioxide; In terms of mass fractions, the first high-temperature frit comprises 62-65 parts of silicon dioxide, 8-10 parts of aluminum oxide, 10-15 parts of calcium oxide, 1-2 parts of magnesium oxide, 3-5 parts of potassium oxide, and 1-2 parts of sodium oxide; the second high-temperature frit comprises 62-65 parts of silicon dioxide, 10-14 parts of aluminum oxide, 8-10 parts of calcium oxide, 1-2 parts of magnesium oxide, 2-6 parts of potassium oxide, 1-3 parts of sodium oxide, and 5-8 parts of zinc oxide; the low-temperature frit comprises 65-68 parts of silicon dioxide, 4-6 parts of aluminum oxide, 6-9 parts of calcium oxide, and 10-15 parts of sodium oxide; Wherein, the mass fractions of the ultrafine aluminum oxide, nano zinc oxide, and nano titanium dioxide are not all 0 at the same time; The particle size of the ultrafine silicon dioxide is ≤10 μm; The particle size of the ultrafine alumina is ≤10 μm; The particle size of the nano zinc oxide is ≤100nm; The particle size of the nano titanium dioxide is ≤100nm.

2. The ceramic glaze according to claim 1, characterized in that: The first high-temperature molten block further comprises, by weight, 0 to 0.2 parts of ferric oxide, 0 to 0.1 parts of titanium dioxide, 0 to 2 parts of zinc oxide, and 0 to 6 parts of barium oxide; And / or, by weight, the second high-temperature fused block further comprises 0-0.2 parts of ferric oxide and 0-0.1 parts of titanium dioxide; and / or, by weight, the low-temperature fused block further comprises 0-0.2 parts of ferric oxide, 0-0.1 parts of titanium dioxide, 0-1 parts of magnesium oxide, 0-2 parts of potassium oxide, and 0-2 parts of zinc oxide.

3. The ceramic glaze according to claim 1, characterized in that: The particle size of the nano zinc oxide is 30 to 60 nm; And / or, the specific surface area of ​​the nano zinc oxide is greater than 4m / g; And / or, the particle size of the nano titanium dioxide is 30 to 60 nm; And / or, the specific surface area of ​​the nano titanium dioxide is greater than 4m / g.

4. The ceramic glaze according to claim 3, characterized in that: The specific surface area of ​​the nano zinc oxide is 4 to 7 m / g; and / or the specific surface area of ​​the nano titanium dioxide is 4 to 7 m / g.

5. A method for preparing a glaze slurry of a ceramic glaze according to any one of claims 1 to 4, characterized in that: The following steps are involved: The ceramic glaze is mixed into a ball mill according to the raw material ratio and wet-milled to obtain the glaze slurry.

6. The method for preparing glaze slurry according to claim 5, characterized in that: In the glaze slurry, particles with a particle size of less than 10 μm account for 90-95% of the total weight of the glaze slurry.

7. A composite glaze, characterized in that: The composite glaze comprises a base glaze and a surface glaze, wherein the surface glaze is applied on the upper surface of the base glaze; The base glaze comprises an opalescent glaze, which comprises, by mass fraction, 60-65% silicon dioxide, 8-12% aluminum oxide, 10-14% calcium oxide, 1-2% magnesium oxide, 2-4% sodium oxide, 5-12% zirconium dioxide, 0-1.2% iron oxide, 0-2% potassium oxide, and 0-0.5% silicon dioxide; The glaze comprises the ceramic glaze according to any one of claims 1-4.

8. A method for preparing a ceramic product, characterized in that: The following steps are involved: providing a blank; applying a glaze slip of an underglaze to the body, the underglaze comprising an opacified glaze; Applying a glaze slurry of a top glaze onto the base glaze, the top glaze comprising the ceramic glaze according to any one of claims 1 to 4; After the glazing is completed, the ceramic product is fired in a kiln to obtain the ceramic product.

9. The method for preparing a ceramic product according to claim 8, characterized in that: The thickness of the glaze layer of the bottom glaze is 0.4 to 0.6 mm; And / or, the glaze layer thickness of the top glaze is 0.1 to 0.2 mm; And / or, the firing temperature in the kiln is 1185-1210°C, the holding time is 10-30 minutes, and the firing cycle is 13-18 hours.

10. A ceramic product, characterized in that: The method is prepared by any one of claims 8 to 9.

11. The ceramic product according to claim 10, characterized in that The roughness of the glaze surface of the ceramic product is 0.015-0.025 μm, and the contact angle is 5-10°.

Citation Information

Patent Citations

  • Matt antifouling cover glaze, matte antifouling ceramic tile and preparation method of matte antifouling ceramic tile

    CN116282925A